Nexus of the Location of Performance of an Obligation as the Basis of Jurisdiction in the Brussels I bis Regulation in Cases Versus Air Carriers - Jacek Gołaczyński; Marek Zalisko (LeXonomica, 2021)
As it is correctly emphasized by the European Union (EU) legislator, actions in the field of air transport should aim, among other things, at ensuring a high level of protection for passengers. The paper attempts to discuss the nexus of the location of performance of an obligation as the basis of special jurisdiction in the context of the Brussels I bis Regulation in cases versus air carriers. A passenger’s choice of special jurisdiction based on the nexus of the location of performance of an obligation in the context of Brussels I bis Regulation, applicable to cross-border matters between Member States supersedes general jurisdiction based on the place of domicile of an air carrier. The nexus of the location of performance of an obligation in cross-border disputes resulting from a contract of air transport made between a passenger and an air carrier as a rule enables the passenger to bring an action in a court based in the location of arrival or departure of the flight.Povzetek. Kot pravilno poudarja zakonodajalec Evropske unije (EU), morajo biti ukrepi na področju zračnega prometa med drugim namenjeni zagotavljanju visoke ravni varstva potnikov. Prispevek poskuša obravnavati povezavo kraja izpolnitve obveznosti kot podlago za posebno pristojnost v okviru uredbe Bruselj I bis v zadevah proti letalskim prevoznikom. Potnikova izbira posebne pristojnosti na podlagi neksusa kraja izpolnitve obveznosti v okviru Uredbe Bruselj I bis, ki se uporablja za čezmejne zadeve med državami članicami, nadomešča splošno pristojnost na podlagi kraja stalnega prebivališča letalskega prevoznika. Povezanost kraja izpolnitve obveznosti v čezmejnih sporih, ki izhajajo iz pogodbe o zračnem prevozu, sklenjene med potnikom in letalskim prevoznikom, potniku praviloma omogoča, da vloži tožbo pri sodišču v kraju prihoda ali odhoda leta.